The C-type lectin receptor Dcir (Clec4a2) restrains Aspergillus fumigatus elimination by limiting the degranulatory activity of neutrophils - Yoshikawa, Fabio Seiti Yamada; Yabe, Rikio; Torigoe, Shota; Yamasaki, Sho; Saijo, Shinobu (Frontiers in Immunology, 2025)
IntroductionC-type lectin receptors (CLRs) are innate sensors crucial for antifungal and antimycobacterial responses, contributing to host defenses against pathogens, including the ubiquitous mold Aspergillus fumigatus. Dendritic cell immunoreceptor (Dcir) modulates immune responses by limiting the development of inflammation and autoimmunity; however, its involvement in fungal infections has not been previously established.MethodsWild-type and Dcir-knockout C57BL/6J mice were infected with A. fumigatus intratracheally to establish a model of pulmonary aspergillosis. For in vitro analysis, neutrophils were purified from the bone marrow and incubated with A. fumigatus hyphae.ResultsMice lacking Dcir exhibited improved clearance of A. fumigatus from the lungs, while tissue inflammation—assessed by phagocyte recruitment and inflammatory cytokine levels within the lungs—did not change significantly compared to Dcir competent mice. Neutrophils from Dcir-deficient mice exhibited enhanced killing of A. fumigatus hyphae, attributed to higher degranulatory activity, triggered by intracellular Ca2+ mobilization.DiscussionThe results indicate a potential association between Dcir and downregulation of signalling pathways associated with neutrophil exocytosis. Thus, Dcir is a potential novel fungal sensor that, unlike other CLR family members, primarily fine-tunes host effector responses.